Color preference for infant's wear of mothers in selected pediatric clinics in Quezon City - Tud, Sharlina Kate M.; Cortes, Graciella T. (2007)
This research is a pilot study aimed to to explore how consumers, or more specifically mothers, select colors for infant's wear. It intended to present in a collection the colors preferred for infant's wear. It also aimed to explore which factors greatly affect the mothers' choice of colors so that their color selection process can be better understood. Data was collected through the interviews with selected respondents. The interviews were conducted at different pediatric clinics in Quezon City. Mothers with children from 0-1 year of age were chosen to be respondents. A guide questionnaire was used during the interviews to facilitate the collecting of information. The interview explored the respondents' profile, shopping practices, color preferences, and the factors that affect their color selection process. The colors preferred by the respondents were soft, pastel colors for both boys and girls. It was also acknowledged that the main factors that affected the respondents' choices were he type of fabrics used in a garment, the occasion for wearing the garment, and the season in which the garment will be worn. A compilation of the preferred colors for both boys and girls was also accomplished. All the information gathered here will contribute to the understanding of color usage in infants wear. This would be of great help to designers, manufacturers, and other Clothing Technologists in the industry.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Infants -- Clothing; Color in clothing